Factors Influencing Career Selection of Accounting Students as Public Accountants (Case Study on Accounting Students in Surakarta) - Anwar Sholeh Ash Shidiq; Wijayanti, Rita (Majapahit Journal of Islamic Finance and Management, 2025)
This study investigates the factors influencing accounting students' career choice to become Public Accountants, focusing on students from universities in Surakarta. Using a quantitative approach, data were collected via an online questionnaire from 100 purposively selected students from the 2021 cohort onward. Six variables were examined: career exposure, self-competence, financial rewards, work environment, social values, and market factors. Results from multiple linear regression show that only self-competence and social values significantly influence students’ interest, while other factors such as financial rewards and work environment were not significant—possibly due to students’ limited exposure to real workplace conditions or misaligned expectations. Although the model passed validity and reliability tests, the limited sample scope may affect generalizability. Future studies should consider broader, randomized samples and incorporate qualitative methods to explore these dynamics more deeply.